Properties of magnetized Quark-Hybrid Stars - Orsaria, Milva Gabriela (2011)
The structure of a magnetized quark-hybrid stars (QHS) is modeled using a standard relativistic mean-field equation of state (EoS) for the description of hadronic matter. For quark matter we consider a bag model EoS which is modified perturbatively to account for the presence of a uniform magnetic field. The mass-radius (M-R) relationship, gravitational redshift and rotational Kepler periods of such stars are compared with those of standard neutron stars (NS).